2019
DOI: 10.4314/jab.v135i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Traditional uses, phytochemical study and morphological characterization of <i>Pistacia lentiscus</i> L. fruits from three areas of northern Algeria

Abstract: Physico-chemistry of the Biological Materials and Biodiversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…These studies have revealed the importance of medicinal plants as natural sources of antidiabetic bioactive agents. P. lentiscus (lentisk or mastic tree), a medicinal plant growing in the wild in the Mediterranean area [ 13 , 14 ] and belonging to the Anacardiaceae family, is traditionally used to treat hypertension, cough, sore throat, eczema, stomach ache, toothache, kidney disorders, jaundice [ 15 ], skin problems and diarrhea [ 16 , 17 ], but also diabetes [ 18 ]. In the ethnobotanical investigation on antidiabetic plants conducted in Morocco by Bouyahya et al (2021), it was revealed that lentisk leaves were the most used part.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have revealed the importance of medicinal plants as natural sources of antidiabetic bioactive agents. P. lentiscus (lentisk or mastic tree), a medicinal plant growing in the wild in the Mediterranean area [ 13 , 14 ] and belonging to the Anacardiaceae family, is traditionally used to treat hypertension, cough, sore throat, eczema, stomach ache, toothache, kidney disorders, jaundice [ 15 ], skin problems and diarrhea [ 16 , 17 ], but also diabetes [ 18 ]. In the ethnobotanical investigation on antidiabetic plants conducted in Morocco by Bouyahya et al (2021), it was revealed that lentisk leaves were the most used part.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the chemical profile and antibacterial properties of essential oils of Lavandula stoechas and Pistacia lentiscus have mainly been examined (Alejandro et al, 2015;Boudieb et al, 2019). However, work on other significant biological activities of essential oils and hydroalcoholic extracts of these two Algerian medicinal plants is limited.…”
Section: Introductionmentioning
confidence: 99%